The Sussex Downs murder - Bude, John, 1901-1957 (A British Library crime classic, 2015)
Already it looked as if the police were up against a carefully planned and cleverly executed murder, and, what was more, a murder without a corpse! Two brothers, John and William Rother, live together at Chalklands Farm in the beautiful Sussex Downs. Their peaceful rural life is shattered when John Rother disappears and his abandoned car is found. Has he been kidnapped? Or is his disappearance more sinister- connected, perhaps, to his growing rather too friendly with his brother's wife? Superintendent Meredith is called to investigate- and begins to suspect the worst when human bones are discovered on Chalklands farmland. His patient, careful detective method begins slowly to untangle the clues as suspicion shifts from one character to the next.